Parto domiciliario: incidencia factores Predisponentes y complicaciones Materno - Neonatal Saposoa 1.993 - Peñaherrera Cárdenas, Ethel M. (1994)
The present study was conducted in the town of Saposoa and aimed to identify factors that determine the home birth and complications that entails to determine behaviors for better health care. The population was selected through non-probability sampling and deliberate study in order to capture the full home births occurring during the mesesde March to August 1993. The study found that activities for maternal health oriented community are still not widespread. Much remains to try and learn. It is clear however, that appropriate training is needed close supervision and communication between all maternal health services and the community. Therefore the realization of care delivery by empirical staff, better prepared through adequate supervision to ensure the early detection of risks, allow therefore extend coverage without loss of effectiveness and possible additional benefits from a more culturally acceptable and satisfactory to the community actually care. All this is possible if there is dedication renewed recognition that life binomial Mother - Child is fundamental.